A Stable Chichibabin Diradicaloid with Near‐Infrared Emission - Chang, Xingmao; Arnold, Mona E.; Blinder, Rémi; Zolg, Julia; Wischnat, Jonathan; Slageren, Joris; Jelezko, Fedor; Kuehne, Alexander J. C.; Delius, Max (Angewandte Chemie International Edition, 2024)
Conjugated molecules with multiple radical centers such as the iconic Chichibabin diradicaloid hold promise as building blocks in materials for quantum sensing and quantum information processing. However, it is a considerable challenge to design simple analogues of the Chichibabin hydrocarbon that are chemically inert, exhibit high diradical character and emit light at a distinct wavelength that may offer an optical readout of the spin state in functional ensembles. Here we describe the serendipitous discovery of the stable TTM‐TTM diradicaloid, which exhibits high diradical character, a striking sky‐blue color and near‐infrared (NIR) emission (in solution). This combination of properties is unique among related diradicaloids and is due to the presence of hydrogen and chlorine atoms in “just the right positions”, allowing a perfectly planar, yet predominantly benzenoid bridge to connect the two sterically stabilized radical centers. In‐depth studies of the optical and magnetic properties suggest that this structural motif could become a mainstay building block of organic spin materials. A stable analogue of the iconic Chichibabin hydrocarbon was synthesized by Ullmann coupling from a readily available, chlorinated trityl radical (TTM‐I). Thanks to its planar bridge, which exhibits hydrogen and chlorine atoms in just the right positions, the TTM‐TTM diradicaloid has skyblue color in solution, emits in the NIR range but nevertheless has significant diradical character at room temperature.